Pop-Eschatology: Reconstructing Islamic Death Narratives in Sal Priadi’s ‘Gala Bunga Matahari’ - Siti Mahmudah Yanti (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
The rapid digitalization of religion has transformed Islamic communication, enabling pop culture to function as an alternative spiritual vessel. This study examines the representation of da’wah values in “Gala Bunga Matahari” by Sal Priadi, a viral Indonesian song, to analyze how theological messages are encoded in secular pop music. Employing a qualitative approach with Ferdinand de Saussure’s structural semiotics, the research focuses on the dyadic relationship between signifier (lyrics) and signified (concept) to uncover latent spiritual meanings. Data were collected through close reading and purposive sampling of key verses, then analyzed using syntagmatic and paradigmatic dimensions. The findings reveal that the lyrics construct a coherent system of signs representing Islamic eschatology specifically the concept of Barzakh and the afterlife phrased not through explicit religious jargon but through metaphors of nature (sunflowers) and eternal longing. The song reframes death not as a frightening end, but as a continuity of love. The study concludes that this work transcends mere entertainment, serving as a new theological medium for Gen Z. It offers a non-dogmatic approach to understanding mortality and Rida (acceptance), proving that digital pop culture can effectively bridge the gap between rigid orthodoxy and the spiritual needs of contemporary Muslim youth.